Non-invasive assessment of hepatic mitochondrial metabolism by positional isotopomer NMR tracer analysis (PINTA). Issue 1 (December 2017) - Perry, Rachel; Peng, Liang; Cline, Gary; Butrico, Gina; Wang, Yongliang; Zhang, Xian-Man; Rothman, Douglas; Petersen, Kitt; Shulman, Gerald
Abstract Hepatic mitochondria play a central role in the regulation of intermediary metabolism and maintenance of normoglycemia, and there is great interest in assessing rates of hepatic mitochondrial citrate synthase flux (V CS ) and pyruvate carboxylase flux (V PC ) in vivo. Here, we show that a positional isotopomer NMR tracer analysis (PINTA) method can be used to non-invasively assess rates ofV CS andV PC fluxes using a combined NMR/gas chromatography-mass spectrometry analysis of plasma following infusion of [3-13 C]lactate and glucose tracer. PINTA measuresV CS andV PC fluxes over a wide range of physiological conditions with minimal pyruvate cycling and detects increased hepaticV CS following treatment with a liver-targeted mitochondrial uncoupler. Finally, validation studies in humans demonstrate that theV PC /V CS ratio measured by PINTA is similar to that determined by in vivo NMR spectroscopy. This method will provide investigators with a relatively simple tool to non-invasively examine the role of altered hepatic mitochondrial metabolism. Liver mitochondrial metabolism plays an important role for glucose and lipid homeostasis and its alterations contribute to metabolic disorders, including fatty liver and diabetes. Here Perry et al. develop a method for the measurement of hepatic fluxes by using lactate and glucose tracers in combination with NMR spectroscopy.